Design and development of testing kit for KNX devices reliability and performance measurement - Mohammad Aizam, M.A.R; Lee, M.F.; Sanusi, N.A; Siew, P.W.; Johnson Lim,, S.C.; Tee, Boon Tuan (2024)
In the dynamic realm of building automation, the reliability and performance of KNX devices are crucial for the uninterrupted functionality of intelligent buildings. This paper presents an essential solution—a dedicated testing kit tailored for the KNX industry. Committed to elevating the quality and efficacy of KNX devices, our project develops a comprehensive testing suite designed to enable manufacturers, system integrators, and industry experts to thoroughly evaluate the reliability, latency, response times, network congestion management, and interoperability of KNX devices. Through an exhaustive analysis of current products’ strengths and limitations, and by addressing the industry’s unique demands, our project resolves prevalent technical challenges within the KNX ecosystem. The testing suite, a synergy of hardware and software advancements, offers an intuitive interface for test configuration and execution. It incorporates standardized test scenarios, data analytics, and reporting capabilities to ensure KNX devices adhere to exacting performance criteria. Moreover, the project underscores scalability, affordability, and versatility, catering to the varied requirements of industry participants. The projected outcomes transcend the creation of a testing apparatus; they include fostering enhanced quality benchmarks, streamlining the manufacturing workflow, diminishing interoperability issues, and ultimately, boosting the overall robustness and efficiency of KNX devices. As the global trend moves towards intelligent, eco-friendly edifices, the “Design and Development of Testing Kit for KNX Devices Reliability and Performance Measurement” initiative aspires to drive innovation and set new standards of excellence in building automation technology.